Effectivité juridique des instruments de protection des espaces naturels appliquée aux projets routiers en France - Fanny Mallard; Denis François (VertigO)
Some major changes to natural environments are related to the construction and the use of roads. In France, despite legal commitments, each year natural areas are disrupted. Forty-three legal instruments of natural areas protection and environmental assessments have been identified and classified according to the hierarchy of rules applicable under French law. A comprehensive and detailed classification of these national, European and international instruments is presented. Highlights the complex structure of the whole system, often contradictory or redundant. The effectiveness of the whole legal framework in protecting natural areas relative to road projects is analyzed on the basis of official legal texts and case law. The Natura 2000 network appears to be the most effective and relevant instrument. However, its applicability is limited in light of the EU requirements. National instruments are generally legally ineffectual. Among the natural areas, forest is the best protected by binding instruments. Despite the effectiveness of the protection offered by few instruments, overall they have failed to stem the loss of biodiversity. Establishing nature sanctuaries and enforcing existing instruments are necessary short term means of improvement. Introducing the concept of green and blue networks of the Grenelle law II could compensate today shortcomings of conservation, provided it based on coercive obligations. Environmental assessment instruments – including EIA – have a disappointing reach and they occur relatively late in the decision process. These instruments do not yet incorporate the ecosystem concept. This can be explained by the lack of an ecological assessment tool of the impacts of projects at the opportunity stage.